Pulmonary Alveolar Microlithiasis - Shaw, Brian M.; Shaw, Steven D.; McCormack, Francis X. (Seminars in Respiratory and Critical Care Medicine, 2020)
Pulmonary alveolar microlithiasis (PAM) is a rare, autosomal recessive disorder that is caused by mutations in SCL34A2 that encodes for the type IIb sodium-dependent phosphate cotransporter (Npt2b). The loss of Npt2b transporter function from alveolar epithelial cells results in failure to export inorganic phosphate from the alveolar lining fluid, which then accumulates, binds to calcium, and forms hydroxyapatite microliths. Radiographs and computed tomography of the chest demonstrate hyperdense infiltrates that are often quite dramatic and distinctive, and in many cases, the diagnosis can be made without invasive measures. The most common presenting symptom of PAM is dyspnea on exertion, but the disease is frequently first noted as an incidental finding in asymptomatic patients who have chest films performed for unrelated reasons. Pulmonary fibrosis, pulmonary hypertension, and respiratory failure can develop as the disease progresses, and treatment remains supportive. Lung transplantation is an option for those with end stage disease.
Keywords: pulmonary alveolar microlithiasis; pulmonary ossification; pulmonary calcification; type IIb sodium-dependent phosphate cotransporter; Npt2b; NaPi-2b; SCL34A2